OPTIMASI SUHU ANNEALING GEN tetM DARI BAKTERI Staphylococcus aureus PADA PASIEN ULKUS DIABETIK - ., Givien Yangwa Krismoni (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Staphylococcus aureus is the dominant gram-positive bacterium found in diabetic ulcer patients. This bacterium has a resistance strain known as MRSA (Methicillin-Resistant Staphylococcus aureus) which has been resistance to the antibiotic Methicillin. MRSA strains in Staphylococcus aureus have resistance to many antibiotics such as tetracycline that used to treat diabetic ulcer patients. Staphylococcus aureus has the tetM gene as a resistance gene that is found on the extra chromosome called plasmid. The selection of appropriate antibiotic therapy for diabetic ulcer patients is needed, therefore it is necessary to identify it using a PCR (Polymerase Chain Reaction) method in vitro with annealing temperature optimization. This research aims to optimize the annealing temperature to obtain resistance genes using forward 5 '-GGGCATCAAGCAA CATTTC-3' and reverse 5 '-TCGAGGTCCGTCTGAACTTT-3' primers with temperatures of 57 ° C, 58 ° C and 60 ° C for 30 seconds. The results of this research were obtained tetM gene with a size of 366 bp using annealing temperature of 60 ° C for 30 seconds and no tetM gene was obtained using annealing temperature of 57 ° C and 58 ° C. The conclusion of this research is the 60 ° C annealing temperature is the optimal temperature to obtain the tetM gene that causes resistance to tetracycline antibiotics in Staphylococcus aureus bacteria.